ظاهرة التَّشدد وعلاجها في ضوء السّنة النبوية - Samer Najeh Samarh (Universiti Sains Islam Malaysia, 2024)
This research aims at shedding the light on the phenomenon of extremism and its treatment in the light of the Sunnah by collecting and studying hadiths related to the subject to attain a perception of the prophetic approach in dealing with this ill, namely: prevention and treatment. The research has elucidated the concept of extremism and its relationship with other concepts related to delving deeper and exaggeration and revealed the main reasons driving the person to be extreme and practice it. Besides, the research showed the means of the Prophetic Sunnah to treat and eliminate extremism through an integrated plan based on two methods; (1) Prevention of extremism through warning against it and explaining its negative consequences to the individual and society as well, (2)Treatment of extremism if occurring by correcting the extremist's understanding through guiding him or her to the methods and means that help them continue their doings, and ending with punishing the extremists based on his or her condition and his or her impact on the community around him.